Isolation, Phenotypic Characterization and speciation of Vancomycin Resistant Enterococci from Clinical Samples - Bhardwaj, Muskan; Reddy, Siva Prasad (Journal of Neonatal Surgery, 2025)
Background:Vancomycin-resistant enterococci (VRE) represent a growing concern in nosocomial infections due to limited treatment options and their intrinsic and acquired antimicrobial resistance. This study focused on the isolation, phenotypic characterization, and speciation of VRE from diverse clinical samples collected at a tertiary care center in Northern India. Objectives:To identify and differentiate Enterococcus species from clinical specimens, determine their antimicrobial susceptibility patterns, and estimate the prevalence of vancomycin resistance among these isolates. Methods:A cross-sectional observational study was conducted from June 2023 to September 2024. Enterococci were isolated using conventional culture methods from blood, urine, pus, cerebrospinal fluid, and other body fluids. Biochemical tests and selective media such as bile esculin azide agar and potassium tellurite agar were used for speciation. Antimicrobial susceptibility testing was performed by the Kirby–Bauer disk diffusion method according to CLSI M100 standards. Vancomycin resistance was confirmed using vancomycin screen agar. Results:A total of 259 Enterococcus isolates were recovered; Enterococcus faecalis constituted 65.25% (n=169) and Enterococcus faecium 34.75% (n=90). The isolates predominantly originated from urine (47.8%) and blood (21.6%). Vancomycin resistance was observed in 4.1% of E. faecalis and 3.3% of E. faecium isolates. High resistance rates were noted for erythromycin (64.6%), penicillin (59.8%), and ampicillin (36.7%). Linezolid, teicoplanin, and vancomycin retained high sensitivity (>95%) among isolates. Conclusion:E. faecalis was the predominant species isolated with a low but notable prevalence of vancomycin resistance. Judicious antibiotic use, early detection, and strict infection control measures are essential to controlling the spread of multidrug-resistant enterococci in healthcare settings